Assembling a 'good' and 'bad' night's sleep: A multifactorial proposition. Issue 4 (27th September 2021) - Ogeil, Rowan P.; Nguyen, Mai‐Tram; Savic, Michael; Lubman, Dan I.
Abstract: Introduction: There is increasing demand for effective sleep health and promotion strategies that are accessible to the general population. Sleep hygiene has traditionally focused on promoting behaviours that facilitate good sleep and avoiding behaviours that interfere with sleep. However, simply following good sleep hygiene practices has proven largely ineffective in clinical samples suffering insomnia, and effectiveness of these recommendations in the general population has also been questioned. One reason for this may be the lack of consideration with respect to interactions between these different factors, as many elements determine a 'good' and a 'bad' night's sleep. Methods: The present paper utilised a mixed methods approach using a combination of framework approach thematic analysis (qualitative) and the number of mentions of different characteristics defining a good and bad night's sleep (quantitative) in participants' ( N  = 282 (157 females), mean age 27 years) accounts of their last good and bad night's sleep, and how (if at all) alcohol or drugs played a role. Results: We found that both good and bad night's sleep were influenced by multiple factors and that often the same factors were implicated in both. A significant number of participants described elements of the sleep episode (e.g., timing pre‐ vs. post‐ midnight, consistency of routine, sleep onset latency, sleep environment), or other behavioural or environmental factors (e.g., alcohol or drug use, mood, food consumed prior to sleep) they perceived were involved in their experience of a good or bad night's sleep. Conclusions: Rather than isolating factors as is typically done in sleep hygiene principles, or viewing these factors as discrete and/or having predictable effects on sleep, it is important to examine how these factors coalesce to shape a good and bad night's sleep.